Teachers' practices during COVID-19: Practices and perspectives in elementary and secondary settings. Issue 1 (2022) - Traga Philippakos, Zoi A.; Rocconi, Louis; Blake, Katherine; Summers, Jessica
Abstract: COVID-19 affected modes of instruction and instructional processes across K to 12 classrooms. The purpose of this study was to examine K-12 teaching practices in one large district during COVID-19 and whether there were differences in overall practices, affect, and confidence, and regarding remote teaching between elementary and secondary teachers. Further, their professional development experiences were examined and their evaluation of those. 97 PreK to grade 12 teachers completed a survey regarding their confidence and affect to teach writing and reading, and provide remote instruction. Teachers also shared specific practices they engaged in during remote instruction and when working with special education and English Language Learners, described the types of professional development they received, their evaluation of their experience, and commented on their college-preparation. Overall, teachers did not find remote instruction of writing and reading as effective, but they commented on the potential of online instruction to be continued after the pandemic if they were provided with adequate support. Further, differences were found between elementary and secondary teachers on their affect and confidence for teaching writing and reading but not for remote instruction. Finally, teachers' comments indicate the need for ongoing PD to address instructional and implementation needs. Implications for research, practice, and policy are discussed. Highlights: Elementary and secondary teachers did not find remote instruction of writing and reading as effective. Elementary and secondary teachers differed on their confidence to teach writing and reading. Even though teachers received professional development on remote instruction, this was not sufficient. Teachers expressed concerns and opportunities about student learning in remote settings. Teachers expressed challenges with perceptions about teaching as a profession and their role as professionals.